Selective Photocatalytic Oxidation of Glycerol and 3-Pyridinemethanol by Nanotube/Nanowire-Structured TiO2 Powders Obtained by Breakdown Anodization - Çetinkaya, Sıdıka; Khamidov, Gofur; Özcan, Levent; Palmisano, Leonardo; Yurdakal, Sedat (Frontiers in Chemistry, 2022)
Nanotube/nanowire structured TiO2 was formed on the Ti surface by anodic oxidation method performed at different potential values (50-60 V) and for different times (3 or 5 hours). The TiO2 powders were taken in powder form using the ultrasonic treatment from the Ti electrodes, calcined at different temperatures, and characterized by XRD, SEM, and BET techniques. Both the crystallinity and the size of the primary TiO2 particles increased by increasing the heat treatment temperature. While all the catalysts heat treated up to 500 °C were only in the anatase phase, the particles heat-treated at 700 °C consisted of both anatase and rutile phases. The BET surface area of the samples decreased drastically after heat treatment of 700 °C because of partial sinterization. SEM analyses indicated that the prepared materials were structured in both nanotubes and nanowires. They were tested as photocatalysts for the selective oxidation of glycerol and 3-pyridinemethanol under UVA irradiation in water at room temperature and ambient pressure. Glyceraldehyde, 1,3-dihydroxyacetone, and formic acid were determined as products in glycerol oxidation, while the products of 3-pyridinemethanol oxidation were 3-pyridinemetanal and vitamin B3. Non-nanotube structured commercial TiO2 (Degussa P25 and Merck) catalysts were used for the sake of comparison. Low selectivity values towards the products obtained by partial oxidation were determined for glycerol. On the contrary, higher selectivity values towards the products were obtained (total 3-pyridinemetanal and vitamin B3 selectivity up to ca. 90%) for the photocatalytic oxidation of 3-pyridinemethanol. TiO2 catalysts must be highly crystalline (calcined at 700 °C) for effective oxidation of glycerol, while for the selective oxidation of 3-pyridinemethanol it was not necessary to obtain a high crystallinity, and the optimal heat treatment temperature was 250°C. The prepared catalysts showed lower activity than Degussa P25, but a greater selectivity towards the products found.